2015
DOI: 10.1002/ange.201506797
|View full text |Cite
|
Sign up to set email alerts
|

Stable Co‐Catalyst‐Free Photocatalytic H2 Evolution From Oxidized Titanium Nitride Nanopowders

Abstract: Abstract:In the present work, a simple strategy is used to thermally oxidize TiN nanopowder (~20 nm) to an anatase phase of a TiO 2 :Ti 3+ :N compound. In contrast to the rutile phase of such a compound this photocatalyst provides photocatalytic activity for hydrogen evolution under AM1.5 conditions -this without the use of any noble metal co-catalyst. Moreover the photocatalyst is active and stable over extended periods of time (tested for 4 months). Importantly, to achieve successful conversion to the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…89,147 Follow-up work demonstrated that similarly active cocatalytic centers can be introduced by alternative approaches. 36,39,40,51,150,151 For example, high-energy proton ion-implantation was used to modify TiO 2 nanotubes selectively at their tops, and in the proton-implanted region, the creation of such intrinsic cocatalytic sites was observed, which were active for photocatalytic H 2 evolution. Proton implantation can induce specific defects and a characteristic modification of the electronic properties not only in nanotubes but also in anatase single crystal (001) surfaces (reaching cocatalyst-free solar H 2 evolution rates of ∼15 and ∼0.2 μmol h −1 cm −2 , respectively).…”
Section: Surface Reactivity In Reduced Tio 2 Singlementioning
confidence: 99%
See 1 more Smart Citation
“…89,147 Follow-up work demonstrated that similarly active cocatalytic centers can be introduced by alternative approaches. 36,39,40,51,150,151 For example, high-energy proton ion-implantation was used to modify TiO 2 nanotubes selectively at their tops, and in the proton-implanted region, the creation of such intrinsic cocatalytic sites was observed, which were active for photocatalytic H 2 evolution. Proton implantation can induce specific defects and a characteristic modification of the electronic properties not only in nanotubes but also in anatase single crystal (001) surfaces (reaching cocatalyst-free solar H 2 evolution rates of ∼15 and ∼0.2 μmol h −1 cm −2 , respectively).…”
Section: Surface Reactivity In Reduced Tio 2 Singlementioning
confidence: 99%
“…The high-temperature, highpressure (500 °C, 20 bar) hydrogenation of anatase or mixed anatase/rutile TiO 2 produced unique catalytic sites that enabled cocatalyst-free hydrogen production rate that were 2 orders of magnitude higher than those observed for stoichiometric powders, reaching values of more than 200 μmol g −1 h −1 . Later on, other synthetic procedures, such as high energy ion implantation, 39 hydride ball milling, 38 and partial oxidation of TiN powders, 40 have been shown to produce similar reduced TiO 2 varieties producing hydrogen without any addition of noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…As an accurate tool to detect the unpaired electron spins, electron paramagnetic resonance (EPR) was used to further probe Ti 3+ species over the hydrogenation time (Figure 2b). The g-tensor of 1.996 assigned to the Ti 3+ species can be observed in hydrogenated samples, 19 while the EPR signal in the P25 sample is absent. Furthermore, the EPR signal of the H-120 sample is stronger than that of the H-15 sample, which confirms the generation of Ti 3+ species during hydrogenation.…”
mentioning
confidence: 99%
“…As evident from Figure 2e , all the Ti 1−x Ru x O 2 precursors exhibit typical phonon lines of the layered titanate phase, [ 33 ] whereas the RTN materials show phonon lines characteristic of the TiN phase, indicating a nitridation‐induced phase transition to rocksalt‐type titanium nitride structure. [ 20 , 21 , 34 ] The increase in Ru content led to gradual displacement of the acoustic phonon line at ≈200 cm −1 toward higher wavenumbers. Because the energy of this Raman peak is proportional to the concentration of nitrogen vacancies, [ 35 ] the increase in the phonon energy with increasing Ru content can be interpreted as further evidence for the creation of nitrogen vacancies caused by the exsolution of Ru nanoparticles.…”
Section: Resultsmentioning
confidence: 99%